PENERAPAN TEORI KEUANGAN MODERN: FAKTOR DETERMINAN NILAI PERUSAHAAN PADA INDUSTRI FOOD AND BEVERAGE - Triani, Triani; Adnanti, Wenny Ana; Khobir, Fatkhul (Universitas YPPI Rembang, 2024)
The study aims to determine the effect of Capital Structures, Profitability, and Firm Size of Company Value in food and beverage companies listed on the Indonesia Stock Exchange. The data used was obtained from the company’s audited financial statements on the Indonesia Stock Exchange during the study period. The population of this research is the companies in the food and beverage sector during 2019-2021 which amount 92 companies. Based on certain criteria there are 18 samples by using purposive sampling method. Method of analysis used was multiple linear regression analysis using SPSS program. The result showed the Capital Structure and Profitability have positive significant effect on company value in food and beverage companies listed on the Indonesia Stock Exchange during 2019-2021. While the Company Size does not affect the value of the company value in food and beverage companies listed on the Indonesia Stock Exchange during 2019-2021